KABA SABAI DALAM PERTUNJUKAN TEATER “PRAY FOR SABAI” - Dedi Darmadi; Koes Yuliadi; Sahrul Sahrul (Institut Seni Indonesia Padang Panjang, 2016)
ABSTRACT Drama or theater is one part. The term of drama is more focused on the literary elements (manuscript, text, story elements), while the term of theater points out the issues on staging/presentation (performing arts and acting). In theatrical performance “Pray for Sabai,” it discussed about a daughter’s revenge for her father’s death. This theme was depicted on the conflicts emerging in the story. The first conflict was when Rajo Nan Panjang intended to propose Sabai Nan Aluih. The second conflict was when Rajo Nan Panjang’s proposal was rejected by Sabai Nan Aluih’s father, Rajo Babandiang. This lead to a fight between Rajo Nan Panjang and Rajo Babandiang that resulted on the death of Rajo Babandiang. Her father’s death made Sabai exacting a revenge on Rajo Nan Panjang. This issue provided an understanding on the morale and ethics of a daughter in Minangkabau namely a woman who fought to defend her family’s dignity and pride from the person who has killed her parent. The reflection of Sabai’s attitude gives perspective on the morale and ethics of Minangkabau people’s life at that time.